The Influence of Compensation and Work Discipline on Employee Performance at Rahayu Building Store, Kediri City - Nisa, Zahria Ula; Sustiyatik, Enni; Pangastuti, Ria Lestari (Universitas Hang Tuah, 2025)
This study aims to determine the simultaneous and partial influence of Compensation and Work Discipline on Employee Performance at the Rahayu Building Store in Kediri City. This quantitative study aims to test the hypothesis with numerical data. All employees of the Rahayu Building Store in Kediri City (36 people) were sampled through saturated sampling techniques because the number of populations and samples was the same. Data analysis was carried out using multiple linear regression. The results showed that compensation did not have a significant effect on employee performance partially, with a significance value of 0.312 (> 0.05). On the other hand, work discipline had a positive and significant effect partially, indicated by a significance value of 0.006 (< 0.05) and a t-count of 2.967> t-table 2.035. Simultaneously, compensation and work discipline had a significant effect on employee performance based on the F test with a significance value of 0.021 (< 0.05). The most dominant variable was work discipline, as evidenced by the highest standard beta coefficient (0.460) and a lower significance value than compensation.